2018
DOI: 10.3390/fi10050041
|View full text |Cite
|
Sign up to set email alerts
|

Route Availability as a Communication Quality Metric of a Mobile Ad Hoc Network

Abstract: Using ad hoc communication between mobile terminals, MANETs (mobile ad hoc networks) are independent of any communication infrastructure but their communication quality can degrade because, as terminals move about in the service area, routes are constantly disconnected and then re-established. There has been no proposal for a quality metric that models this unstable state, i.e., route nonuniformity. This paper proposes a new concept of route availability (RA) as a metric of route nonuniformity in a MANET and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, Chhagan Lal et al [20] proposes a Multi-Constraint QoE-centric Routing technique (MCQR) for efficient real-time video streaming over Mobile Ad-hoc Networks. In contrast, [21] worried about the instability of MANET routing, proposes a Route Availability (RA) as a new metric for route non-uniformity, while analyzing its impact on QoS and, eventually, on QoE. With similar objectives in sight, our paper shall also aim for the enhancement of the QoE related to video streaming services over MANETs, with a particular focus on node mobility within said networks; for it is no secret that this very feature (mobility) is a double-edged factor, the successful management of which can make or break the entirety of a high-fidelity video streaming framework.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, Chhagan Lal et al [20] proposes a Multi-Constraint QoE-centric Routing technique (MCQR) for efficient real-time video streaming over Mobile Ad-hoc Networks. In contrast, [21] worried about the instability of MANET routing, proposes a Route Availability (RA) as a new metric for route non-uniformity, while analyzing its impact on QoS and, eventually, on QoE. With similar objectives in sight, our paper shall also aim for the enhancement of the QoE related to video streaming services over MANETs, with a particular focus on node mobility within said networks; for it is no secret that this very feature (mobility) is a double-edged factor, the successful management of which can make or break the entirety of a high-fidelity video streaming framework.…”
Section: Introductionmentioning
confidence: 90%
“…The throughput condition means to achieve the minimum threshold with the highest throughput of the entire route among candidate. A new concept of route availability was presented in [19] as a measurement of route no uniformity in a MANET as it represents the QoS or QoE of video streaming. They confirmed two QoS metrics and founded that route availability is affected by changes in video quality.…”
Section: Introductionmentioning
confidence: 99%
“…A new concept of route availability was presented in [16] as a measurement of route no uniformity in a MANET as it represents the QoS or QoE of video streaming. They confirmed that RA had a linear correlation with the two QoS metrics and founded that RA is more affected by the video quality.…”
Section: Introductionmentioning
confidence: 99%